Urban and Rural Secondary High School Students' Perceptions On Drug Awareness Programs - Imanova, Sevinj; Mammadova, Minara; Hajiyeva, Umida (ADA University, 2024)
Drug addiction among adolescents is a significant global challenge, with serious consequences for their health, education, and overall wellbeing. This thesis investigates the perceptions and awareness of secondary high school students in both urban and rural areas of Azerbaijan regarding drug awareness programs. The study also evaluates the strategies employed by schools to promote drug awareness and prevention. Through qualitative research, including interviews with students, teachers, and administrators, the thesis provides insights into the effectiveness and reach of existing programs in diverse educational settings. The findings suggest that while urban schools may benefit from better resources and external support, rural schools face significant barriers, including limited budgets, lack of trained personnel, and insufficient educational materials. The research highlights the importance of context-specific interventions and underscores the need for enhanced cooperation between schools, local authorities, and communities in tackling drug misuse among adolescents. By analyzing both the successes and challenges of current programs, this thesis offers recommendations for improving drug awareness and prevention efforts across Azerbaijan’s educational institutions.
Keywords: Rural schools -- Azerbaijan; Adolescents -- Drug use -- Prevention; Azerbaijan -- Education -- Secondary schools; Urban schools -- Azerbaijan; Education